The effect of mobile application usage on dialect perception - Zakaria, R.; Mansor, N.R.; Ibrahim, M.Y.; Rashid, R.A.; Zakaria, R.; Ismail, M.S.; Abdullah, N.A.C.; Arifin, R.M.; Razak, M.T.A.; Ahmad, A.S. (2020)
The extent of mobile application usage roles in language dialect retention has roused curiosity and called for research. The fast-paced world that we are living in today has resulted in many effects with regard to the use and retention of a subject including how dialects are used. This concept paper talks in general about the significance and effect of using mobile applications on dialect and language. The use of mobile applications in most cases has become a very handy tool for every business. We have to admit that it is a time-saving, financial, and information-sharing system that makes things go faster and travel more efficiently. The study of mobile application in many parts of the world involves the use of qualitative and quantitative methods so that more accurate and scientific results can be extracted. Our goal is to look at the impact and importance of using mobile applications to retain the dialect used in particular and the use of language in general. The findings of the study have brought us to two conditions with good and bad consequences on the use of both dialect and language. The vast education system that we have in particular has demonstrated the significant use of mobile applications. As everything requires a very efficient and efficacious financial system its significant is irefutable. The results shown here will boost the improvement in language learning and dialect retention via a multitude of mobile applications. The use of both methods in carrying out mobile application review have been getting some very good responses.